Efektivitas Bahan Peningkat Penetrasi, Isopropil Miristat Dalam Krim Antioksidan Ekstrak Biji Kasumba Turate (Carthamus tinctorius L.) - Ermina Pakki; Muzakkir Rewa; Nur Irma (STIFA Makassar, 2019)
The research concerning on the effectiveness of isopropyl myristate as a penetration enhancer agent against diffusion rate of antioxidant creams containing lyophilizates kasumba turate seed (Carthamus tinctorius L.) extract using Franz diffusion method had been done. This research aims to determine the optimum concentration of isopropyl myristate in kasumba turate antioxidant cream. Started with the sample preparation, the seeds of kasumba turate were extracted using infusion method, lyophilized and specified its total polyphenol. As regard the lyophilization process, the lyophilizates were formulated into W/O cream with varied concentration of isopropyl myristate at 1% (FII), 5% (FIII), 10% (FIV) w/w and used cream without isopropyl myristate as negative control. Physical stability of creams was evaluated both before and after stressed conditional storages and used Franz diffusion instrument to observe the penetration ability of creams. As the result, all creams are physically stable. Furthermore, FIII and FIV have good penetration manner, especially FIV using 10% isopropyl myristate as a penetration enhancer agent in lyophilizates kasumba turate cream has the greatest polyphenol flux and cumulative amount.